STRATEGY TO INCREASE PRODUCTIVITY OF 20-25 YEAR AGE PALM OIL PLANTS AT PT.PP LONDON SUMATRA BAGERPANG ESTATE - Ari Gunawan; Eka Bobby Febrianto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to formulate a strategy to increase the productivity of oil palm plantations at PT PP London Sumatera Bagerpang Estate. The study was conducted from November 2025 to April 2026 using a qualitative descriptive method supported by a SWOT analysis. Data collection was conducted through field observations, interviews with plantation management and employees, and secondary data in the form of production data, plant population, fertilization, pest and disease control, and harvest reports. Data analysis was carried out by identifying internal and external factors using a SWOT matrix. The results showed that the actual productivity of oil palm plantations in 2025 decreased by 2.02 tons/ha . The main strength factors consisted of the application of rorak and mounding (score 0.84), the availability of heavy equipment (0.48), and accurate plantation administration (0.23). Weakness factors included low Stand Per Hectare (SPH) (0.49), minimal technical supervision (0.39), and inadequate water gate conditions (0.34). Meanwhile, the main opportunities come from the availability of local labor (0.90) and the proximity of the area to water sources (0.49). The results of the SWOT analysis place the company in Quadrant IV (defensive strategy) , so the recommended strategy is to maintain SPH through mounding activities, rorak construction , water gate repair , optimization of mechanical maintenance, and community involvement in garden maintenance activities. The implementation of this strategy is projected to increase average productivity from 14.99 tons/ha to 20.58 tons/ha , or an increase of 4.20 tons/ha .